1996
DOI: 10.1002/j.1460-2075.1996.tb00910.x
|View full text |Cite
|
Sign up to set email alerts
|

Misdivision analysis of centromere structure in maize.

Abstract: The size and organization of a representative plant centromere from the supernumerary B chromosome were determined using a repeated sequence specific to the centric region. Several derivatives of the B chromosome that suffered from misdivision of the centromere were analyzed for the content and organization of their B repeat. In all these derivatives, major rearrangements were detected. Some misdivisions produced a significant reduction in size of the B‐specific cluster. These results demonstrate that the B re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(67 citation statements)
references
References 40 publications
2
65
0
Order By: Relevance
“…The A. thaliana centromere regions are rich in repetitive DNAs, which is a hallmark of the molecularly characterized centromere regions from humans (Willard and Wayne 1987), mice (Kipling et al 1991;Narayanswami et al 1992), maize (Alfenito and Birchler 1993;Kaszás and Birchler 1996), Drosophila (Le et al 1995;Murphy and Karpen 1995), Neurospora (Centola and Carbon 1994), and fission yeast (Nakaseko et al 1986;Clarke 1990). A. thaliana centromeres contain long arrays of 180-bp repeats with little or no interspersion, in addition to the more complex arrays of 180-bp repeats mixed with other repeat elements characterized previously (Richards et al 1991;Pelissier et al 1996;Thompson et al 1996a,b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The A. thaliana centromere regions are rich in repetitive DNAs, which is a hallmark of the molecularly characterized centromere regions from humans (Willard and Wayne 1987), mice (Kipling et al 1991;Narayanswami et al 1992), maize (Alfenito and Birchler 1993;Kaszás and Birchler 1996), Drosophila (Le et al 1995;Murphy and Karpen 1995), Neurospora (Centola and Carbon 1994), and fission yeast (Nakaseko et al 1986;Clarke 1990). A. thaliana centromeres contain long arrays of 180-bp repeats with little or no interspersion, in addition to the more complex arrays of 180-bp repeats mixed with other repeat elements characterized previously (Richards et al 1991;Pelissier et al 1996;Thompson et al 1996a,b).…”
Section: Discussionmentioning
confidence: 99%
“…The current physical maps of the A. thaliana genome based on overlapping genomic clones do not represent the large 180-bp arrays described here, and we believe that the centromeres are missing from these maps (Schmidt et al 1995;Zachgo et al 1996). It may be necessary to analyze A. thaliana centromeres that have been pared down in subchromosomal derivatives rather than rely on assembly of centromeric regions from constituent genomic clones Brown et al 1994;Le et al 1995;Murphy and Karpen 1995;Kaszás and Birchler 1996).…”
Section: Genome Researchmentioning
confidence: 91%
“…Analysis of a normal plant centromere from the supernumerary B chromosome of maize (Alfenito and Birchler 1993;Kaszas and Birchler 1996) indicated that this centromere spans ∼9 Mb and is composed of a sequence repeat, highly degenerate in length but that has a plurality unit of 1.4 kb. Part of this repeat shows strong homology to a maize neocentromere unit sequence of 90 bp.…”
Section: Comparison Of Known Centromeric Sequencesmentioning
confidence: 99%
“…Analysis of the B chromosome of maize provided a demonstration that the repetitive sequences at plant centromeres are included in the functional kinetochore (Alfenito and Birchler 1993;Kaszas and Birchler 1996). By using successively rearranged chromosomes caused by centromere fission or misdivision, the central portion of the B centromere was displaced to a new location.…”
Section: Comparison Of Known Centromeric Sequencesmentioning
confidence: 99%
See 1 more Smart Citation